(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Perichondritis refers to an inflammation of the perichondrium, a layer of connective tissue which surrounds cartilage. Auricular perichondritis, the commonest form, involves the pinna due to infection of a traumatic or surgical wound or the deep spread of superficial inflammation. This type of disease often leads to residual deformity, and its incidence in our experience seems to be increasing. Objectives: The present study was conducted to determine the predisposing factors, pathogenic organisms, interventions and residual deformities of the disease in a peripheral medical college hospital. Methods: This was a prospective study which was conducted in the Department of Otolaryngology – Head & Neck Surgery, Pabna Medical College Hospital, Pabna from January 2017 to June 2018. Follow up was for six months ending with assessment of pinna deformity. Data was analyzed using SPSS for windows version 22. Results: Patients were from 15- 75 years of age (range 60 years) with male predominance and peak in the fourth decade of life. The most common predisposing factors were trauma from motor vehicle accidents (30%) followed by high ear piercing (22%). Pseudomonas aeruginosa (48%) followed by Staphylococcus aureus (20%) were the most common organisms. Patients were treated with intravenous antibiotics but 76% also required surgical intervention. 68% developed residual deformities of the pinna with 50% being total and 18% being partial. Conclusion: Auricular perichondritis is a frightening disease which requires early management. As Pseudomonas aeruginosa is the most common organism, antipseudomonal antibiotics should be started as early as possible. Despite medical and surgical intervention, residual deformities may ensue. Bangladesh J Otorhinolaryngol 2022; 28(2): 165-170